MsrA repair of Cytochrome c and α‐crystallin links chaperone and oxidative repair pathways with mitochondrial protection and apoptotic control in lens cells - KANTOROW, M; BRENNAN, L; MCGREAL, R; LEE, W; DAVID, L; GIBLIN, F (Acta ophthalmologica (Oxford, England), 2010)
Purpose Methionine sulfoxide reductase A (MsrA) is essential for lens defense against oxidative stress and cataract formation through its ability to repair oxidized protein methionine (PMSO). Here, we examined α‐crystallin and cytochrome c (Cyt c) as potential targets for MsrA‐repair in the lens. Methods The oxidized methionine content of α‐crystallin and Cyt c was evaluated from the lenses of MsrA knockout and w+ mice. The activities of α−crystallin and Cyt c were evaluated upon methionine oxidation. The ability of MsrA to repair these proteins and restore their respective chaperone and electron transport activities was determined. All three proteins were localized in lens cells and their abilities to form complexes in vitro and in vivo evaluated. Results Cyt c was oxidized at met 80 and αβ‐crystallin at met 68 in MsrA‐knockout relative to w+ mice. Methionine oxidization of 138 of αA‐crystallin and 68 of αB‐crystallin resulted in loss of α‐crystallin chaperone function while oxidation of met 80 resulted in loss of Cyt c electron transport function. α‐crystallin protected Cyt c against methioinine oxidation. MsrA repaired and restored the functions of all three proteins which co‐localized and formed complexes in lens mitochondria. Conclusion MsrA is likely required for repair of α‐crystallin and Cyt c in lens cells suggesting that it maintains and regulates the activities of α‐crystallin and Cyt c in lens mitochondria where all three proteins were localized. Loss of MsrA‐repair could contribute to cataract formation through loss of chaperone function, loss of oxidative phosphorylation and/or increased Cyt c mediated apoptosis.